The Color Representation of Death: A Study of Death Flag Color in Javanese Culture - ayu, diajeng; Asprillia, Anandya (Universitas Brawijaya, 2024)
The study of color in anthropolinguistics is continuously growing as it relates to language and local culture. Several colors such as yellow, white, green, red, and black are the representation of the death flag in Javanese culture. Through this study, we attempt to examine most of the death flags and the understanding of its meaning in the Javanese community. The sample of the study was taken from 100 participants of the Javanese people in Malang, Surabaya, and Gresik. We interviewed them based on our questionnaire regarding the color of the death flag in Javanese community. The results show yellow being the most common death flag in Javanese, even though most cultures associated black with sadness or grief. This phenomenon leads to cross-cultural discussion regarding Javanese people perceiving the colors of the death flag outside of their intended meaning.